AN INVESTIGATION LONG-TERM RELATIONSHIP BETWEEN STOCK MARKETS: THE CASE OF TURKEY, CHINA, INDIA AND PAKISTAN - UÇAR, İbrahim Halil; ALSU, Erkan (SSD Journal, 2022)
The correlation and long-term relationship between stock markets are important for global investors who aim low risk and high return through portfolio diversification in global stock markets. Therefore, knowledge of co-integration between stock markets is an important factor for optimal portfolio diversification. In the study the long-term relationship between Borsa Istanbul and SSE, SZSE composite, Nifty50 and Karachi 100 indices was investigated with the Autoregressive Distributed Lag Model (ARDL) by using 192-monthly closing data of indices for the period 1 January 2006- December 31 2021. As a result of the study it has been found that Borsa İstanbul was cointegrated with the stock markets of SSE and SZSE composite (China), Karachi100 (Pakistan) and Niffty50 (India) in the long run. Besides the high positive correlation and long-term relationship between BİST100 index and Nifty50, Karaçi100 indexes indicate that Borsa İstanbul is affected by these markets. Therefore, it is seen that these markets are not suitable for global investors who aim to reduce risk and increase returns by diversifying their portfolios in global markets